2021
DOI: 10.1084/jem.20210583
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic innate immune response determines susceptibility to SARS-CoV-2 infection and early replication kinetics

Abstract: Initial replication of SARS-CoV-2 in the upper respiratory tract is required to establish infection, and the replication level correlates with the likelihood of viral transmission. Here, we examined the role of host innate immune defenses in restricting early SARS-CoV-2 infection using transcriptomics and biomarker-based tracking in serial patient nasopharyngeal samples and experiments with airway epithelial organoids. SARS-CoV-2 initially replicated exponentially, with a doubling time of ∼6 h, and induced int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
134
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(185 citation statements)
references
References 87 publications
13
134
4
Order By: Relevance
“…Our findings indicate that the host response to SARS-CoV-2 in nasal epithelium is dominated by paracrine IFN-I/III signalling, albeit this response is kinetically delayed. These data contrast with initial reports that SARS-CoV-2 did not induce a robust IFN response in airway epithelial cells 2628 , but are consistent with emerging evidence of IFN- I/III induction in nasal swabs from patients with COVID-19 15, 4244 and with more recent findings in lung airway models 36, 43, 45–47 . Blockade of the endogenous IFN response had an impact on SARS-CoV-2 infection at later stages post-infection, once the IFN response was established, underscoring the delayed kinetic but also emphasising its functional relevance.…”
Section: Discussionsupporting
confidence: 57%
“…Our findings indicate that the host response to SARS-CoV-2 in nasal epithelium is dominated by paracrine IFN-I/III signalling, albeit this response is kinetically delayed. These data contrast with initial reports that SARS-CoV-2 did not induce a robust IFN response in airway epithelial cells 2628 , but are consistent with emerging evidence of IFN- I/III induction in nasal swabs from patients with COVID-19 15, 4244 and with more recent findings in lung airway models 36, 43, 45–47 . Blockade of the endogenous IFN response had an impact on SARS-CoV-2 infection at later stages post-infection, once the IFN response was established, underscoring the delayed kinetic but also emphasising its functional relevance.…”
Section: Discussionsupporting
confidence: 57%
“…In conclusion, it appears that physically (or chemically) inactivated viral particles are not sufficient to induce a strong antiviral immunity, in contrast to “live” but propagation-incompetent IAV DIPs. Furthermore, infection with rhinovirus before SARS-CoV-2 in vitro can also result in an accelerated ISG responses and a prevention of SARS-CoV-2 replication [ 61 ]; yet, fully infectious and propagation-competent rhinovirus was used, which may result in unfavorable side effects. With respect to the safety of IAV DIPs for potential clinical application, it is important to note that administration of only active DIPs did not cause apparent toxic effects in mice and ferrets [ 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both studies emphasize the suitability of measuring expression of selected ISGs in nasal swab material as a good correlative to early nasopharyngeal virus replication. Whereas Lopez et al (2021) employed an ISG score set by expression of four ISGs (IFI27, IFI44L, RSAD2, IFIT1), Cheemarla et al (2021) found that measurement of the chemokine CXCL10 alone is sufficient to report viral loads.…”
mentioning
confidence: 99%
“…In their efforts to understand the importance of the IFN system in the nasopharyngeal epithelium, Cheemarla et al (2021) took a different approach. These authors argued that the occurrence of multiple viruses and nonviral microbes in the upper respiratory tract is a frequent occurrence in asymptomatic subjects.…”
mentioning
confidence: 99%